Measuring Motivation Orientation and School Readiness in Children Served by Head Start. (3rd April 2019) - Bustamante, Andres S.; Greenfield, Daryl B.
Abstract: Currently, the most widely used direct assessment of motivation orientation for preschoolers has little to no research on its reliability and validity. This study examined the test–retest reliability and concurrent and predictive validity of this direct assessment. Results highlight potential limitations of this measure in capturing motivation orientation in preschoolers from low-income families.